Architecture Ecologised: Nature’s Patterns and Abstractions in Malay Built Traditions - Ismail Jasmani; Norzalifah Zainal Abidin; Shamzani Affendy Mohd Din; Puteri Shireen Jahn Kassim (Universitas Indraprasta PGRI, 2019)
The following paper discusses analysis and morphology of key motifs and patterns drawn from a range of cases in Malay architecture and built form, which arise of centuries of observation of nature and its eventual artistic expressions in building elements. They focus on patterns found in many traditional buildings repeatedly across the Nusantara. These patterns, taken from flora and fauna of the region, recall how woodcarvers, artisans and builders were inspired by the living beings which they found surrounding them. The paper highlights that these nature-related motifs represent a ‘regionalising’ aesthetic strategy, which vary in terms of location, and which builders and patrons of architecture used to regionalize and ‘localise’ their buildings and cases. The hand-drawn motifs in the study were thenrelated to the symbolic and spiritual meaning of them, highlighting that these meaning could be again re-instated in modern architecture. The motifs could represent a spiritual and regional means of re-infusing the built environment with a ‘soul’ and meaning, in the midst of modernization and urbanization.